BUDAYA “Sulang-sulang Hariapan” Pada Masyarakat Batak Toba Dalam Memaknai Titah Ke-lima - Iwantri Lumbangaol; Albiner Siagian; Rencan C. Marbun (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
Abstract. One of the legacies of the ancestors in the Toba Batak culture is the Manulangi ritual. One of the Manulangi rituals in Toba Batak society is currently known as Sulang-sulang Hariapan. Hariapan toasts in Batak society are known as a way of honoring elderly parents. Respecting parents is an implementation of the fifth law of the Torah contained in Exodus 20:12: "Honor your father and mother, so that your days may be long in the land that the Lord your God is giving you." In Christian teaching, we teach respecting parents, not speaking harshly, not insulting parents, especially when they are sick, but parents must be given encouragement so that even when they are sick, they remain calm and wait for death to come. Every child who respects his parents will receive blessings. The author uses a qualitative approach. The Qualitative Approach emphasizes the search for meaning, understanding, concepts and descriptions of a phenomenon; prioritizes quality, and is presented narratively. Research data was collected through interviews. The author conducted open interviews so as not to limit the informants from conveying their understanding of Sulang-sulang Hariapan. This research was conducted in Sungai Raya Village, Siempat Nempu Hulu District, Dairi Regency. The results of research conducted by the author on traditional figures, religious leaders and ordinary people in Sungai Raya Village in performing the Hariapan Toasts are the result of interpreting the meaning of the Fifth Commandment, even the Hariapan Toasts are the result of a theological study of the Fifth Commandment.